The effect of the social environment during childhood on preferences in adulthood - Johannes Abeler; Toke Reinholt Fosgaard; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2023)
Preferences are key for shaping decision-making, yet it remains an open question where preferences originate from. We investigate the causal effect of the childhood social environment on adults' preferences. We utilize a natural experiment in Denmark, which randomized refugees to different neighbourhoods in the 1990s. We experimentally measure risk, time, and social preferences of adult refugees who were children at the time of arrival in Denmark. Using rich administrative register data on the entire Danish population we can measure a very broad range of aspects of the childhood social environment. We find that the randomly allocated childhood environment significantly affects adults' preferences, in particular, patience.
Keywords: C90; D15; D64; D81; D90; J62; 330; Preference formation; natural experiment; register data